The Characteristic of Sandy Soil’s Shear Strength with Lime and Coal Fly Ash Mixture - Ibnu Toto Husodo (International Conference on Coastal and Delta Areas, 2017)
Sandy soil in solid conditions tends to have good characteristics. However, sand in the even and loose and water-saturated conditions has low shear strength when cyclic load occurs (such as earthquake). This paper presents the results of research on the improvement of sandy soil with a mixture of lime and coal fly ash. Two mixing techniques on the sandy soil were done in column (method A) and mixed (method B). Coal fly ash - lime mixture was done with a ratio of 1: 1 (in weight ratio). An unconsolidated undrained triaxial test was performed for both methods at the test of 1 day, 3 days, 7 days and 14 days. The size of the triaxial test specimen was diameter = 36 mm and height = 72 mm. For method A, the column was made as high as the test specimen with a diameter size of 12 mm. The shear strength value of unstable sand was 35.4 kPa. Overall, it can be concluded that stabilization techniques affect the shear strength of sandy soil. The soil improvement technique with method B gives a larger shear strength value than method A does. However, sand soil behavior with improved technique of method B is more brittle than method A. Keywords: strong shear, sand, coal, lime, triaxial